Mustahik Zakat Dalam Islam - Muzayyanah MUzayyanah; Heni Yulianti (Fakultas Syariah dan Ekonomi Islam Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2020)
This study examines the status of orphans in receiving zakat Throughout the author's research from Islamic books and references that orphans do not become obligatory alms. Zakat mustahik people who are entitled to receive zakat assets. A person is not entitled to receive zakat (not considered as mustahik), except for an independent Muslim (not a slave), not a member of the Bani Hasyim or Bani Muttalib tribe, and must have one of the eighth asnaf (group) characteristics. in the Qur'an. In other words, zakat may not be distributed to unbelievers, people who are still slaves, or a member of the Bani Hasyim and Bani Muttalib tribes. As mentioned in the Qur'an at-Taubah [9]: 60, those who are entitled to receive zakat (Mustahik zakat). This is the verse used as the argument, that the recipients of zakat are 8 groups. And do not include that orphans as zakat alms.